Ectodermal dysplasias: New perspectives on the treatment of so far immedicable genetic disorders - Schneider, Holm (Frontiers in Genetics, 2022)
The past decade has witnessed an expansion of molecular approaches facilitating the differential diagnosis of ectodermal dysplasias, a group of genetic diseases characterized by the lack or malformation of hair, teeth, nails, and certain eccrine glands. Moreover, advances in translational research have increased the therapeutic opportunities for such rare diseases, and new dental, surgical, and ophthalmic treatment options are likely to offer relief to many individuals affected by ectodermal dysplasias. In X-linked hypohidrotic ectodermal dysplasia (XLHED), the genetic deficiency of the signaling molecule ectodysplasin A1 (EDA1) may even be overcome before birth by administration of a recombinant replacement protein. This has been shown at least for the key problem of male subjects with XLHED, the nearly complete absence of sweat glands and perspiration which can lead to life-threatening hyperthermia. Prenatal treatment of six boys by injection of an EDA1 replacement protein into the amniotic fluid consistently induced the development of functional sweat glands. Normal ability to sweat has so far persisted for >5 years in the two oldest boys treated in utero. Thus, timely replacement of a missing protein appears to be a promising therapeutic strategy for the most frequent ectodermal dysplasia and possibly additional congenital disorders.